Struvite crystallisation and recovery using a stainless steel structure as a seed material. - Le Corre, Kristell S.; Valsami-Jones, Eugenia; Hobbs, Phil; Jefferson, Bruce; Parsons, Simon A. (Elsevier Science B.V., Amsterdam., 2007)
A metallic system acting as a seed substrate has been designed and developed in order to assess its efficiency in recovering phosphorus as struvite. The device, consisting of two concentric stainless steel meshes, was immerged in the upper section of a pilot crystallisation reactor fed with synthetic liquors (MgCl2·6H2O, NH4H2PO4,) for 2 h. Apart from soluble PO4-P removals which remained in the range 79–80% with or without application of the metallic system, it was found that under the specific operating conditions tested the meshes were capable of accumulating struvite at a rate of 7.6 gm−2 h−1, hence reducing significantly the amount of fine particles remaining in solution from 302.2 to 12 mg L−1 when compared to trials with
Keywords: Seeded crystallisation; Struvite; Metallic accumulation system; P removal and recovery